Research on Innovation in Human Resource Management in the Context of a Sustainable Economy - Chen Xi (SHS Web of Conferences, 2024)
Human resource management (HRM) is encountering fresh challenges and possibilities in the sustainable economy. As the world’s attention on environmental protection and social responsibility grows, businesses are reassessing their human resource management strategies and practices to support sustainable development. The innovative human resource management model helps improve employee satisfaction and loyalty and enhances enterprises’ competitiveness and market adaptability. First, businesses must focus on green recruitment by setting standards that prioritize environmental protection and social responsibility to attract talents that are aligned with sustainable development principles. This method not only enhances the company’s reputation but also fosters the sustainable advancement of society. Second, companies can introduce flexible working arrangements, such as telecommuting and flexible working hours, to meet employees’ needs for environmental protection and work-life balance. Furthermore, the organization should prioritize its workforce’s ongoing education and growth. It entails enhancing employees’ understanding and abilities in environmental protection and sustainable practices through comprehensive training programs and fostering an environment that encourages innovation. It is necessary for enterprises to establish an effective performance management system, incorporate sustainable development goals into employee performance appraisal, and ensure that employees will contribute to the sustainable strategy. Implementing the aforementioned innovative management measures allows enterprises to achieve enhanced economic benefits while positively contributing to the sustainable development of society and the environment.